(untitled) (XXI Century. Spanish Literature and Culture, 2017)
The author divides many aspects of human life, including language itself, in a dialectic between the periphery and the center, given a sense of marginality. But, when the time comes, the center realizes that the one who has the real power is that periphery, which will be ‘eaten up’ towards the center, without losing completely its marginal character.